Urbanization and solid waste generation in urban Longleng district of Nagaland: : Present practices and future challenges - Chubakumzuk Jamir (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
Urbanisation is a growing issue in Longleng. So are the consequent solid waste generation and its management challenges. Population growth has a positive impact on urbanization process. This article is intended to explain the common problems facing public services today and the challenges faced by both the urban planners and the government. The paper reviews an overview of solid waste management generation in urban Longleng. Solid waste management which is already an immense task in urban Longleng is going to be more difficult with the expansion of urbanization, increase in consumerism and changing life style. The result shows that residential (59.5%), commercial (20%), institutional (16%), biomedical wastes (0.30%), construction and demolition (4.2%) contribute to solid waste generation. The current practices of dumping waste materials in urban areas have shaped serious environmental and public problems. Financial resources constraints, institutional policies weaknesses, and public indifference towards solid waste have made this situation worse. This research article evaluates the current practices prevalent to deal with this solid waste and problems associated with it. It also provides the measures to deal with this waste in a healthy and environmental manner so that it may prove a resource instead of waste. The results of this study will be of immense benefit for urban-related studies in small towns as well as for the urban planners in the district.